Adoption of innovations in Latin American family farming - Triana Riveros, Jorge Luis (2021)
In this article, a study of the process to adopt an innovation in family farming was carried out, identifying variables of the organizational and institutional environment that influence the adoption process. The article was developed through a literature review, analyzing the main variables that affect adoption, in order to contribute to the strengthening of innovation processes in family farming; and thus, take advantage of the innovations created by our research centers, universities and the private-public sector. They conclude that it is of great importance that research entities make alliances with intermediary institutions to disseminate the knowledge acquired with the aim of not having failure in adoptions